2012
DOI: 10.4149/gpb_2011_04_329
|View full text |Cite
|
Sign up to set email alerts
|

The role of PPAR in myocardial response to ischemia in normal and diseased heart

Abstract: Abstract. Peroxisome proliferator-activated receptors (PPAR), ligand-activated transcription factors, belong to the nuclear hormone receptor superfamily regulating expression of genes involved in different aspects of lipid metabolism, inflammation and cardiac energy production. Activation of PPAR-α isoform by its natural ligands, fatty acids (FA) and eicosanoids, promotes mitochondrial FA oxidation as the primary ATP-generating pathway. On the other hand, PPAR-γ regulates lipid anabolism or storage, while, unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 100 publications
0
25
0
1
Order By: Relevance
“…I/R insult resulted in a drop of PGC-1␣ and NRF transcripts, together with increased transcript levels of genes coding lipid metabolic pathways in C and LTHA hearts, suggesting enhanced lipid utilization at that stage (21,31,55), irrespective of the acclimatory status. The only finding linked with acclimation status was the abolished upregulation of PPAR␥, PPAR␦ (associated with lipid metabolism), and Hadhb (associated iron metabolism) on the STHA mitochondria.…”
Section: Mitochondria Biogenesismentioning
confidence: 99%
“…I/R insult resulted in a drop of PGC-1␣ and NRF transcripts, together with increased transcript levels of genes coding lipid metabolic pathways in C and LTHA hearts, suggesting enhanced lipid utilization at that stage (21,31,55), irrespective of the acclimatory status. The only finding linked with acclimation status was the abolished upregulation of PPAR␥, PPAR␦ (associated with lipid metabolism), and Hadhb (associated iron metabolism) on the STHA mitochondria.…”
Section: Mitochondria Biogenesismentioning
confidence: 99%
“…PPARs are nuclear receptor proteins coupled with retinoid X receptors (RXR) which act as transcription factors to regulate the expression of some genes mostly affecting lipid metabolism and energy balance in cells [13]. These transcription factors have three subtypes: PPAR-a, PPARb/d and PPAR-c, which have different expressions in various tissues [14].…”
Section: Introductionmentioning
confidence: 99%
“…The cell types used (see Methods section for details) were: THP-1 monocytic cells (THP1-Mon), M2-polarized THP-1 monocytes (THP1-M2Mon), PMA-differentiated THP-1 macrophages (dTHP1-MΦ), and M2-polarized PMA-differentiated THP-1 macrophages (dTHP1-M2MΦ). We have previously reported that intercalation of oxLDL-derived cholesterol into the ER membrane of oxLDL-treated THP1-Mon cells alters the physico-chemical properties of this membrane (as determined by Electron Paramagnetic Resonance spectrometry [23]), and so disrupts ER membrane protein function (as determined by coupled-enzyme SERCA2b Ca 2+ ATPase assays [23]).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, UPRs lead either to restoration of normal cell physiology and cell survival, or to cell death [17]. Thus, excessive accumulation of cholesterol into macrophages can lead via UPR/CHOP-triggered apoptosis to lipotoxic macrophage cell death [20,21]; importantly, we and others have recently reported that oxLDL can trigger similar effects [22,23], due to liberation of free cholesterol from oxLDL particles that have been imported into macrophages, and trafficking of this free cholesterol to the ER membrane [16,20,23]. …”
Section: Introductionmentioning
confidence: 99%